Growth and Production Response of Cowbean (Vigna unguiculata (L.) Walp) to Goat Dunge and Straw Mulch Fertilizer Application - Andarula Galushasti; Priyanti, Yani Hasanah; Ilham Muhklisin; Jumiatun (KHD Production, 2026)
Cowpea (Vigna unguiculata (L.) Walp) is a legume with good adaptability to various soil types and drought conditions, offering potential as an alternative protein source to soybeans. This study aimed to investigate the effect of goat manure fertilizer and straw mulch on the growth and yield of cowpea. The research was conducted from August to November 2024 at the agricultural field of Politeknik Negeri Jember using a factorial randomized block design with two factors: goat manure dosage (0, 90, 110, 130, and 160 g/plant) and mulch type (silver mulch and straw mulch), with three replications. Growth parameters and yield components such as plant height, number of pods, pod weight, and seed weight were recorded. The results showed that the application of 160 g/plant goat manure significantly increased plant height at 35 days after planting, the number of pods per plant, wet and dry pod weights, and seed yield, while straw mulch had no significant effect on any variable. No interaction effect was observed between the two treatments. The findings suggest that goat manure application is an effective strategy to enhance cowpea productivity under field conditions without the need for straw mulching.